2021
DOI: 10.1136/bmjopen-2021-049318
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical acupoint stimulation (TEAS) for cancer-related fatigue: study protocol for a systematic review and meta-analysis

Abstract: IntroductionCancer-related fatigue (CRF) is a prevalent symptom in cancer survivors. Transcutaneous electrical acupoint stimulation (TEAS) has been reported as a promising therapy for CRF. This protocol is proposed for a systematic review that aims to assess the efficacy and safety of TEAS for CRF.Methods and analysisCochrane Central Register of Controlled Trials, PubMed, Medline, Embase, Chinese National Knowledge Infrastructure, VIP, Wanfang database, Chinese Biomedical Literature Database, Chinese Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…On the one hand, the human acupoints selected were based on empirical evidence and were not accurately located; on the other hand, the empirical treatment protocols varied greatly with individual patients, which made it hard to assess and verify long-term treatment effects. 13 , 35 , 44 Previous studies 18 , 45 have found that the identification and location of acupoints would become much more operable and independent rehabilitation by patients would become easier under the assistance of the SI technology. That study proposed a new physical therapy that combined meridians in the traditional Chinese medicine, SI, and modern electronic technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, the human acupoints selected were based on empirical evidence and were not accurately located; on the other hand, the empirical treatment protocols varied greatly with individual patients, which made it hard to assess and verify long-term treatment effects. 13 , 35 , 44 Previous studies 18 , 45 have found that the identification and location of acupoints would become much more operable and independent rehabilitation by patients would become easier under the assistance of the SI technology. That study proposed a new physical therapy that combined meridians in the traditional Chinese medicine, SI, and modern electronic technology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because the treatment protocols are not universal and because patients have limited self-awareness towards their own condition, recovery can hardly be continued and the treatment is ineffective. 13 , 14 TEAS studies focus mostly on its effects, while technical innovation in this regard is rarely discussed. The application of somatosensory interaction (SI) in independent rehabilitation with acupoint massage is a new type of sports rehabilitation method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture is also widely used for palliative and supportive care for cancer patients, and it has not only been limited to manual acupuncture but has also incorporated electrical acupuncture, auricular acupuncture, laser acupuncture, etc 8 10 . Based on a large number of recommendations made by clinical practice guideline development groups and expert groups from 13 countries, acupuncture has been recommended for chemotherapy-induced and post-operative nausea and vomiting, cancer pain, fatigue, insomnia, xerostomia, hot flashes, lymphoedema, and chemotherapy-induced neuropathy, as well as to improve the quality of life (QoL) of these patients 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A study by Fang et al [37] suggested that taVNS could significantly normalize the intrinsic connectivity of the DMN in MDD, and Rong et al [38] showed the potential application of VNS treatment for MDD. Transcutaneous electrical cranial stimulation (TECS) is an additional promising therapy for post-traumatic stress disorder and comorbid depression, as well as for cancer-related fatigue [39,40]. Based on the above studies, a new non-invasive stimulation method combined taVNS [37,38], and TECS named transcutaneous electrical cranial-auricular acupoint stimulation (TECAS)was developed showing high patient adherence in the treatment of depression.…”
Section: Introductionmentioning
confidence: 99%